(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Utilization of sandwich composite during recent year has been driven by the fact that composite material has ultimately high strength and stiffness by weight than any other materials. The skins of sandwich composites technically bear most of the applied loads, however, the core materials also play an important role as it functions in providing continuous support to resist the shear stress. Hence, proper selection of core materials is required to establish a sturdy sandwich composite structure. This paper presents an experimental investigation on the sandwich structure consists of fibreglass/epoxy face skins and a mahang wood core. Sandwich composite with core grain oriented in parallel and perpendicular to the flat plane direction were tested for mechanical performance in tension, compression and flexure. The results indicate that sandwich composite with grain oriented in parallel direction performed better in tensile properties with strength of 201.98 MPa whereas sandwich composite with perpendicular core grain produced a higher value of compression properties with strength of 70.11 MPa. However, no significant effect of grain orientation was observed in flexural strength. The strength of sandwich composite is dependent on the grain alignment of the wood core as it functions exclusively as mechanical supporting cells to support the wood structure.